SAE Technical Paper Series 2005
DOI: 10.4271/2005-01-2142
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Turbocharger Catalyst - Fast catalyst light-off evaluation

Abstract: Further tightened emission legislation and new engine technologies increase the requirements for the exhaust after-treatment system of modern diesel passenger cars. Especially the increasing raw emissions of HC and CO as well as the low temperature of the exhaust gas for a long period during cold start of the New European Driving Cycle (NEDC) require additional efforts in the design of the oxidation catalyst system [1]. A highly efficient micro catalyst, which is mounted in front of a turbocharger, can help to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…One proposed solution [1][2][3] to this problem is to place a small catalyst before the turbocharger, where the exhaust temperature is generally about 100°C higher than in the post-turbo position. Owing to space and back pressure considerations, these pre-turbo catalysts must be very small and operate at very short residence times.…”
Section: Introductionmentioning
confidence: 99%
“…One proposed solution [1][2][3] to this problem is to place a small catalyst before the turbocharger, where the exhaust temperature is generally about 100°C higher than in the post-turbo position. Owing to space and back pressure considerations, these pre-turbo catalysts must be very small and operate at very short residence times.…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason to explain these very high efficiencies with small catalyst volumes was that the turbulent flow into the PTC channel leads to a better mass transfer of the pollutants from the gas stream to the active coated walls. This turbulence phenomenon was verified later on by calculation of the mass transfer coefficient ß as a function of the gas speed or catalyst diameter [7]. The influence of the PTC on the main DOC is also presented in [7], with the PTC reducing the pollutant concentrations in the exhaust gas and producing a resultant exotherm, the main DOC gets an earlier light-off and a better overall performance than without a PTC.…”
Section: Ptc Conceptmentioning
confidence: 83%
“…The PTC oxidation functionality has been further proven on Euro III and Euro IV Diesel passenger cars [6,7]. It has been shown that the addition of a PTC (with volume up to 40 ml) in the exhaust line could permit the elimination of the under-floor catalyst of a serial solution made up of a CCC and a UFC (thus reducing by 70% the total volume of the DOC function in this case), or to replace the main Euro IV DOC of an Euro IV vehicle by its prior Euro III part (thus decreasing the PGM loading by 50g/ft³).…”
Section: Experience In the Fieldmentioning
confidence: 99%
“…Another idea is the relocation of the catalytic converter upstream from the turbine. The exhaust gas temperature is at least 50°C higher than that measured downstream from the turbine, which would contribute to a faster achievement of the effective operation of the catalytic converter [8]. In addition, an increase in the temperature of the exhaust gas in the catalytic converter resulting from the exothermic nature of the reactions occurring inside could improve the operating conditions of the turbine, which operates in a five-stroke engine at a relatively low temperature.…”
Section: Discussionmentioning
confidence: 99%